"Samopomoc Chłopska" w Kartuzach sprzedaje i wymienia zboże siewne. (Kartuzy : [s.n.], 1948)
Afisz z inf. o cenach.
Keywords: Rolnicy -- Polska -- 1945-1970.; Zboża -- ceny -- Polska -- 1945-1970.; Kartuzy (Polska) -- 1945-1970 -- druki ulotne